Efectividad de una estrategia educativa en salud oral en niños de edad escolar con discapacidad auditiva de la Institución educativa Normal Superior de Neiva (2022)
Introduction: Children with hearing impairment have a higher probability of suffering deficiencies in their oral hygiene compared to a child without disabilities. Objective: To evaluate the effectiveness of the "Smiling Chameleon Take Care of Your Teeth St rategy" in children with and without hearing impairment of the Normal Superior Educational Institution of Neiva". Materials and methods: It is longitudinal study , through which the application of the strategy "Smiling Chameleon and Brave Silk Cuida Tus Die ntes Results: positive impacts were identified in variables such as brush use, achieving a greater knowledge in its importance to reduce caries and eliminate food debris. Conclusions: Other strategies should be considered to improve oral hygiene knowledge, attitudes and practices.